A Sciological Study of 'Sonali Kabin' - Yeasmin, Sabina (Jagannath University Journal of Arts, 2026)
Al Mahmud stands as a significant figure in Bengali poetry of the 1950s, renowned for fusing lyrical aesthetics with sociological insight. Sonali Kabin (1973) is one of his timeless creations. Al Mahmud highlights the economic struggles of rural communities and calls for equitable distribution of agricultural resources. He frequently incorporates elements of folk culture and folk traditions, using them as powerful tools to bridge the gap between the past and the present, thereby making traditional cultural expressions relevant to modern consciousness. As a poet, Al Mahmud is deeply connected to the roots of Bengali identity. His focus on rural life, women, nature, and traditional culture illustrates his dedication to preserving and revitalizing indigenous narratives. His poetic inquisitiveness is ultimately anchored in the socio-economic, political and cultural contexts of his time. By doing so, he not only preserves a collective memory but also questions the structural inequalities of modernity. His fusion of sociological insight with lyrical beauty is rare in the Bengali literary tradition. This paper aims to examine the sociological relevance and transformative role of Sonali Kabin through a historical-analytical approach, highlighting its socio-political underpinnings and literary significance. Jagannath University Journal of Arts, v-15, i-2, 2025:p25-39